Case study of engineering ethics toward natural gas pipeline leaking: An analysis through solving technique - Sulaima, Mohamad Fani; Mohd Zambri, Mohd Khairi; Othman, Md Nazri; Mohd Nasir, Mohamad Na'im; Jali, Mohd Hafiz; Bohari, Zul Hasrizal; Wan Daud, Wan Mohd Bukhari; Ahmad Izzuddin, Tarmizi; Nor, Mohd Khanapiah (Research India Publications, 2014)
This paper focuses on the case study of engineering ethics for Gas Pipeline Explosion at Ghislenghien, Belgium. The tragedy happened on 30th of July, 2004 and investigation was conducted to find the root cause. However, the question is remains unsolved. Investigators and experts listed few reasons that may affecting the gas pipeline including safety regulations not being observed due to deadline given is too short, soil erosion and used of mechanical diggers within one meter of the gas pipe. Rescue operation was initiated immediate after the gas explosion. This tragedy causes 24 dead including 5 fire fighters and indicated an amount of 100 million euros lost and lead to multiple reformation. Therefore, a case study of engineering ethics has been done and the analysis has been made in terms of ethical framework and ethical theories respectively. The recommendation of this study is hoped to help the engineers in order to reduce the numbers of accidentin their work place.